Nursing students bringing first aid to the community - Ramírez-Torres, Carmen Amaia; Andrade-Gómez, Elena; Lozano-Ochoa, Cristina; Caparrós-Civera, María Neus; Sapiña-Beltrán, Esther (Frontiers in Education, 2023)
Aim. This study aimed to evaluate the theoretical and practical skills acquired for the nursing students and school students after the service-learning project. Methods. This study promotes nursing students and school students working together to gain awareness and basic theoretical knowledge of first aid. The learning project was conducted with nursing students (n=67) and school students (n=131) from April to June 2022. The nursing students gave scores higher than 8 to the aspects linked to expectations, self-perception, overall assessment, and attainment of the goals, these results are in line with the qualitative analysis. Results. Moreover, 100% of the school students reported a satisfactory outcome about the service. Conclusion. Service-learning is a challenging and motivating methodology for nursing students which results in greater engagement with theory and practice and the development of essential skills for future professionals.